734 Evaluation of A Webinar Based Surgical Teaching Course (EDUCATE) - A Prospective Cohort Study. (12th October 2021) - Tan, L; Mullins, W; Gargan, K; Shea, J; Brice, J; Gargan, A; Townsend, J; Jang, C; Shukla, S; Asif, A; Fricker, M; Nathan, A; et al.
Abstract: Aim: Anecdotal evidence suggests Foundation Year (FY) doctors start surgical rotations with less confidence than medical rotations. The study aimed to determine the effect of a national webinar-based surgical teaching course on participants' confidence, and to assess attitudes surrounding undergraduate surgical education. Method: This prospective cohort study is reported with reference to STROBE guidelines and received ethical approval. A series of 15 free-access webinars was developed based on the Royal College of Surgeons Undergraduate Curriculum. An expert-validated questionnaire was used to collect data before and after the course. Inclusion criteria were UK-based medical students and FY doctors who attended at least one webinar. The primary outcome was confidence in completing common tasks during surgical rotations. Results: Completed pre-course (484) and post-course (352) questionnaires yielded 92 paired samples (63% female). 85% were medical students, representing 29 UK universities, and 15% FY doctors. Mean confidence in assessing, investigating, and implementing initial management of surgical conditions was greater after the intervention (p ≤ 0.001). Mean confidence in managing on-call tasks and starting a surgical FY job was also higher post-course greater (p ≤ 0.001). These improvements correlated with webinar attendance (p ≤ 0.05). 27.1% of participants were satisfied with the quality of undergraduate surgical education. 22.9% agreed that surgical placements prepared them well to manage surgical tasks. Conclusions: Medical students and FY doctors report low confidence and feel unprepared in managing surgical tasks. Additionally, they report poor satisfaction with undergraduate surgical education. This shortfall may be improved through delivery of a national, accessible, targeted online webinar series and curriculum.